A non‐native earthworm shifts seed predation dynamics of a native weed. Issue 1 (4th October 2021) - Regnier, Emilie E.; Hovick, Stephen M.; Liu, Jianyang; Harrison, Steven Kent; Diekmann, Florian
Abstract: Introduced seed dispersers can shift seed predation dynamics in native species, impacting native plant establishment and spread. We studied the effect of the non‐native earthworm, Lumbricus terrestris, on seed loss dynamics in the large‐seeded native annual, Ambrosia trifida (giant ragweed), an expanding agricultural weed whose seeds are heavily predated by mice. Lumbricus terrestris may protect seeds against rodent predation by caching them in its burrows from which seedlings can emerge unharmed; however, little is known about the ability of earthworms to compete with rodents for seeds. We investigated this interaction and how environmental factors affected the competitive outcome. In a 2‐year field study, we analysed relative rates of seed removal by earthworms and mice for seeds dispersed at various times in habitats that varied in vegetative cover. Species‐specific responses to environmental conditions drove variation in the share of seeds taken by earthworms versus mice, with earthworms gaining relatively more seeds under warmer, wetter conditions and in low plant cover habitats, and mice obtaining more seeds under colder, drier conditions and in high cover habitats. Environmental factors also determined which competitor accessed seeds first, and this conferred a competitive advantage that was compounded over time. Earthworms cached some seeds under all experimental conditions, suggesting that L . terrestris can act mutualistically with giant ragweed in diverse environments. Synthesis and applications . Our results support the hypothesis that the non‐native earthworm Lumbricus terrestris behaves as a seed dispersal mutualist for the native annual giant ragweed by caching its seeds in its burrows, thereby reducing their availability to rodent seed predators. The data also support the view that interactions among the environment and competing seed predators determine the fate of seed pools in response to species‐specific environmental preferences. In crop fields where L . terrestris is abundant, additional efforts to prevent giant ragweed seed return may be warranted due to the likelihood that earthworms will increase giant ragweed soil seed pools. Lumbricus terrestris is expanding its range throughout temperate regions and may similarly affect secondary seed dispersal and seed predation dynamics of large‐seeded species in other plant communities. Abstract : Our results support the hypothesis that the non‐native earthworm Lumbricus terrestris behaves as a seed dispersal mutualist for the native annual giant ragweed by caching its seeds in its burrows, thereby reducing their availability to rodent seed predators. The data also support the view that interactions among the environment and competing seed predators determine the fate of seed pools in response to species‐specific environmental preferences. In crop fields where L . terrestris is abundant, additional efforts to prevent giant ragweed seed return may be warranted due to the likelihood that earthworms will increase giant ragweed soil seed pools. Lumbricus terrestris is expanding its range throughout temperate regions and may similarly affect secondary seed dispersal and seed predation dynamics of large‐seeded species in other plant communities.